(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Compilation, analysis, and update on intervention studies using nutritional products containing probiotics to improve the health conditions of children Subjects and methods: Basic research methods, evaluation criteria, guidelines, and commonly used tools from reputable scientific journals were utilized to analyze and select relevant literature. The sources included reputable medical electronic libraries such as PubMed, Scopus, NCBI, Cochrane Library, as well as search engines like Google Scholar and specialized biomedical and nutrition journals. Priority was given to studies published within the last five years. Results: Studies show that probiotics supplementation can positively support the treatment of functional constipation, acute diarrhea, acute upper respiratory infections, and immune enhancement. However, more large-scale studies with sufficiently long intervention periods are needed to provide more evidence-based recommendations. Conclusion: Probiotics have great potential to improve children’s health and disease. There is a need for innovative new formulations that combine more diverse strains of probiotics and probiotics with nutrients such as vitamins and minerals.